2014
DOI: 10.1111/jog.12356
|View full text |Cite
|
Sign up to set email alerts
|

Local injection of vasopressin reduces the blood loss during cesarean section in placenta previa

Abstract: The local injection of vasopressin into the placental implantation site significantly reduced the blood loss without increasing the morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…19 However, our results were inconsistent with the findings of a previous study, in which the additional effects of carbetocin were presumed to be trivial because of thinning in the lower uterine myometrium, thereby reducing the immunoreactivity of oxytocin receptors relative to the upper part of the uterus. 20 We noted that the significant differences in outcomes between treatments were mainly due to the contributions of the emergency Caesarean section group. Previous studies have largely demonstrated beneficial effects from carbetocin treatment in women undergoing elective Caesarean section, but not in women undergoing intrapartum Caesarean section.…”
Section: Discussionmentioning
confidence: 83%
“…19 However, our results were inconsistent with the findings of a previous study, in which the additional effects of carbetocin were presumed to be trivial because of thinning in the lower uterine myometrium, thereby reducing the immunoreactivity of oxytocin receptors relative to the upper part of the uterus. 20 We noted that the significant differences in outcomes between treatments were mainly due to the contributions of the emergency Caesarean section group. Previous studies have largely demonstrated beneficial effects from carbetocin treatment in women undergoing elective Caesarean section, but not in women undergoing intrapartum Caesarean section.…”
Section: Discussionmentioning
confidence: 83%
“…If invasion extends into the myometrium, the term placenta increta is used; placental invasion beyond the uterine serosa (at times involving the bladder or other pelvic organs and vessels) is termed placenta percreta (5) . Cesarean delivery is essential in nearly all cases of placenta previa and the amount of blood loss during surgery is significantly higher than in cases of normal placental presentation, also the rate of blood transfusion was also significantly increased (6) . Different conventional approaches had been used to stop hemorrhage, including continuous uterine massage, uterine packing, and uterotonic agents, including oxytocin, prostaglandin and ergometrine.…”
Section: Introductionmentioning
confidence: 99%
“…Different conventional approaches had been used to stop hemorrhage, including continuous uterine massage, uterine packing, and uterotonic agents, including oxytocin, prostaglandin and ergometrine. However, in patients with placenta praevia , hemorrhage from the placental implantation site may continue after placental delivery because the lower uterine segment has poorer contraction than the uterine body (6) .There were multiple modalities that have been evolved to minimize blood loss during CS, which had directed towards reducing blood flow to the pelvis through bilateral ligation of internal iliac arteries or their branches (7) .Vasopressin is a naturally occurring hormone produced by magno-cellular neurons in para ventricular and supraoptic nuclei within the hypothalamus and secreted by the posterior lobe of the pituitary gland, where it is stored in granules present in the axon terminals (8) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations